Correction: ThC2@C82versus Th@C84: unexpected formation of triangular thorium carbide cluster inside fullerenes. Issue 3 (3rd January 2023) - Shen, Yi; Yu, Xiaojuan; Meng, Qingyu; Yao, Yang-Rong; Autschbach, Jochen; Chen, Ning
Abstract : Correction for 'ThC2 @C82 versus Th@C84 : unexpected formation of triangular thorium carbide cluster inside fullerenes' by Yi Shen et al., Chem. Sci., 2022, ; https://doi.org/10.1039/d2sc04846a .